Status of library automation of college libraries in Mendiola - Ingles, Shirley A. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1996)
The purpose of this study is to present the status of library automation of college libraries in Mendiola. Specifically it aims: 1) to find out the types of library automation employed, 2) to determine the accessibility of the information to the users through the types of automation employed, 3) to determine the kind of services being offered, and 4) to determine the plans for further improvement and implementation toward automation.
Survey method is employed to study the present status of three (3) college libraries. Questionnaires and interview are utilized as search instruments. Random sampling technique is used to obtain sample from students, faculty and administrators.
Typescript.
Vita.
Thesis (Bachelor of Library Science)--University of the Philippines Diliman
Keywords: Academic libraries -- Philippines -- Manila; Libraries -- Automation. -- Philippines -- Manila